Late Holocene onset of intensive cultivation and introduction of the falaj irrigation system in the Salut oasis (Sultanate of Oman). (15th November 2018) - Cremaschi, Mauro; Degli Esposti, Michele; Fleitmann, Dominik; Perego, Alessandro; Sibilia, Emanuela; Zerboni, Andrea
Abstract: This paper discusses the time and steps of the introduction of intensive agriculture and evolution of irrigation systems to sustain crops in the palaeo-oasis of Salut in the northern Sultanate of Oman. Various geoarchaeological methods allow reconstructing the exploitation of the natural resources of the region and technological development of irrigation methods since the Mid-Holocene. Intensive agriculture started during the Bronze Age and continued with some spatial and intensity fluctuations up to the Islamic period. Cultivations were initially sustained by surface irrigation systems and later replaced by a dense net of aflaj, the typical surface/underground system adopted in the Levant, Arabian Peninsula and western Asia to collect water from deep piedmont aquifers and redistribute it to the fields located in the lowlands. Our results indicate that the aflaj were in use for a long period in the palaeo-oasis formed along Wadi Sayfam and surrounding the citadel of Salut. Uranium-Thorium dating of calcareous tufa formed in the underground tunnels of the aflaj suggests that they were used between ∼540 BCE and ∼1150 CE. After ∼1150 CE Wadi Sayfam were abandoned and the size of the oasis shrank substantially. During the late Islamic period, a surface aqueduct descending from the piedmont of Jabal Shams secured water supply. Our work confirms that in arid lands archaeological and historical communities were able to actively modulate their response to climate changes by using a variety of technological strategies. Highlights: We investigated the onset of intensive cultivation in Northern Oman. Intensive agriculture started in the Bronze Age. Intensive cultivation continued with some fluctuations up to the Islamic period. Cultivations were initially sustained by surface irrigation systems. U/Th dating of calcareous tufa dates back the introduction of the falaj system to the Iron Age.